Dual Binding of an Antibody and a Small Molecule Increases the Stability of TERRA G‐Quadruplex1. (24th November 2014) - Yangyuoru, Philip M.; Di Antonio, Marco; Ghimire, Chiran; Biffi, Giulia; Balasubramanian, Shankar; Mao, Hanbin
Abstract In investigating the binding interactions between the human telomeric RNA (TERRA) G‐quadruplex (GQ) and its ligands, it was found that the small molecule carboxypyridostatin (cPDS) and the GQ‐selective antibody BG4 simultaneously bind the TERRA GQ. We previously showed that the overall binding affinity of BG4 for RNA GQs is not significantly affected in the presence of cPDS. However, single‐molecule mechanical unfolding experiments revealed a population (48 %) with substantially increased mechanical and thermodynamic stability. Force‐jump kinetic investigations suggested competitive binding of cPDS and BG4 to the TERRA GQ. Following this, the two bound ligands slowly rearrange, thereby leading to the minor population with increased stability. Given the relevance of G‐quadruplexes in the regulation of biological processes, we anticipate that the unprecedented conformational rearrangement observed in the TERRA‐GQ–ligand complex may inspire new strategies for the selective stabilization of G‐quadruplexes in cells.